Psicanálise e educação: o sofrimento psíquico dos acadêmicos da Unioeste de Francisco Beltrão-PR - Biesek, Débora Maria (2021)
Qualitative approach research, of an applied nature, explanatory and characterized as a case study, based on the technical procedures used. It is a bibliographical research, a literature review of scientific productions with a psychoanalytical basis on the topic. The analysis of medical records of 32 students from the State University of West Paraná - UNIOESTE - Francisco Beltrão - PR campus, was performed in the extension project entitled Psychological Support Group for Academics - GAPAC - UNIOESTE - Francisco Beltrão-PR campus. The objectives were to analyze the manifestations of the students' psychological suffering and identify the possibilities of intervention in order to promote mental health in the university environment. To achieve the objectives of this bibliographical and exploratory research, we used the Case Study methodology, which seeks to know the phenomenon to be studied in its entirety, considering the complexity of the variables that involve it when exploring a situation deeply. We analyzed the psychic suffering of students in psychological care sessions. We identified that the main source of suffering, identified as the most painful, came from relationships with other human beings. Many academics felt pressured and compelled to give their all because they were occupying a place at a public university. However, some of them reported that they were in an undergraduate course incompatible with their own desire, which contributed to increased suffering. The categories of analysis that emerged from the consultations were related to suicidal ideation, anxiety disorders, difficulty in adapting to studies in higher education and difficulty in living far from family. These symptoms and manifestations of psychological distress were similar to the results found in the literature review. We observed that much of this suffering is related to the subjects' identity. The difficulties, the choices, the tension, the constant lack of pleasure, the feeling of incapacity, the insecurity with the practice, the loss of freedom and moments of leisure affects their notion of totality. These are very distressing situations, which affect the functions of the Self, and consequently, the academic performance of these subjects. Based on the literature review and on the assistance provided at GAPAC, we found possibilities for intervention in this reality, which we grouped into five categories: the institutionalization of student assistance services; teacher training beyond curriculum content; institutional actions; the infrastructure of the university and the use of arts in the teaching methodology. Currently, suffering is the rule at work, in production, in studies. It is used as a political strategy: only those who suffer and succeed have the merit of their achievements, in this contemporary political regime. Psychic suffering is considered immanent to the human being, but it needs to be used to give greater dynamism to the subjects.